Evaluation of the immune response to an mRNA vaccine prototype against COVID- 19: a preclinical study - Jorge, Renan Galuzo Alves de Carvalho (2025)
Fundação Oswaldo Cruz. Instituto de Tecnologia de Imunobiológicos. Rio de Janeiro, RJ, Brasil.